2017
DOI: 10.1021/acs.est.7b02080
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Mass Balance on Fluorine on Papers and Textiles

Abstract: Papers and textiles that are treated with per- and polyfluoroalkyl substances (PFASs) are sources of human and environmental exposure. Data for individual PFASs, such as perfluorooctanesulfonate (PFOS) and perfluorooctanoate (PFOA), are not placed into the context of total fluorine for papers and textiles. Gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were used to quantify volatile and ionic PFASs, respectively, and the total oxidizable precursor (TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
154
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 86 publications
17
154
1
2
Order By: Relevance
“…Thus, the homologue pattern of PFASs in cosmetics appear to follow the same trend as treated textiles and papers where recent studies typically report the highest concentrations and detection frequency for C6 compounds. 37,38,46 Fluorine mass balance and unidentied PFASs CIC spike/recovery experiments involving samples fortied with different combinations of PFOS and NaF (see method section for details) revealed that inorganic uorine was effectively removed during the extraction procedure (i.e. uorine was not detected in samples fortied only with NaF).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the homologue pattern of PFASs in cosmetics appear to follow the same trend as treated textiles and papers where recent studies typically report the highest concentrations and detection frequency for C6 compounds. 37,38,46 Fluorine mass balance and unidentied PFASs CIC spike/recovery experiments involving samples fortied with different combinations of PFOS and NaF (see method section for details) revealed that inorganic uorine was effectively removed during the extraction procedure (i.e. uorine was not detected in samples fortied only with NaF).…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Despite the availability of these analytical platforms, many PFASs lack authentic standards, making them unquan-tiable using the aforementioned approaches. In order to circumvent the problems of multiple MS-based approaches and standard availability, combustion ion chromatography (CIC) [25][26][27][28][29][30][31][32][33][34][35][36] and particle induced gamma ray emission (PIGE) 28,37,38 have recently been introduced for indirect quan-tication of total and extractable organic uorine (TF and EOF, respectively) in samples. As these approaches are uorine-specic, a standard of any uorinated substance may be used for quantication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report by the Organization for Economic Co‐operation and Development (OECD) lists 4730 PFAS‐related CAS registry numbers, an immense quantity to monitor and regulate if handled on a substance‐by‐substance basis (Ritscher et al ). In response, several analytical techniques have emerged over recent years for quantifying total fluorine and/or extractable organic fluorine (EOF) in environmental samples and consumer products, which complement compound‐specific PFAS analysis (Miyake et al ; Yeung et al ; Robel et al ; Schultes et al , ). By combining these data using fluorine mass balance calculations, the fraction of unidentified fluorine in a sample can be estimated (Schultes et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are highly fluorinated chemicals used in a variety of applications and consumer products (Robel et al 2017;Tokranov et al 2018), which can result in their emission to the environment (Wang et al 2017). Due to concerns on environmental and health impacts of PFASs, monitoring surveys have assessed the extent of contamination of aquatic ecosystems (Lindim et al, 2015;Campo et al, 2016;Loos et al, 2017) and water sources (Hu et al, 2016;Boone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%